Analysis of Key Factors Affecting Case-to-Ambient Thermal Resistance in Thermal Modeling of Power Devices - Kaixin Wei; Peiji Shi; Pili Bao; Chuanchao Liu; Yanzhou Qin (Energies)
In the application of power converters, the ambient temperature (Ta) experiences significant fluctuations. For the case-to-ambient resistance (Rca), apart from the influence of the material’s inherent properties, factors such as heat dissipation structure, working environment, and operational state can all have an impact on the Rca. Notably, while there are a limited number of models that consider environmental changes, existing models for calculating the Rca predominantly overlook the influence of varying working conditions or boundary conditions on the self-thermal resistance. Based on simulation and experimental analyses, the methods to calculate the Rca are outlined, and the key factors, inclusive of the coupling effects that influence the Rca in the thermal modeling of power devices, are thoroughly discussed.